Rancangan Pemberdayaan Masyarakat pada Pengelolaan Hutan Kemasyarakatan (HKm) Desa Pacekke, Kecamatan Soppeng Riaja, Kabupaten Barru, Sulawesi Selatan - Nur Awaliyah Reski; Yusran Yusran; Makkarennu Makkarennu (Jurnal Hutan dan Masyarakat, 2017)
The aim of this study is identified needs to improvecommunity capacity and develop community empowerment plan.This study was used interview method, observation, and references.Selection of samples is done by purposive sampling with community criteria incorporated in Forest Farmer Group of MegahBuana and identified the needs of community capacity building through five strategic issues.The five issues i.e.policy, institutional, forest resources, human resources, economy and social.In the final stages community empowerment plan is made where they were in and around forest for minimalize effect of the consequences of these five strategic issues. The results shown that policy issues, there are limited access to forest resources and high public dependence on government programs.So it needs community empowerment policy where it’s transparent, participatory, consistent and targeted to community.In the institutional issues there are poorof public access to capital, markets, science and technology, and the bargaining position of communities in low partnerships, it is necessary to develop institutional capacity based on institutional-based institutional.In the forest resource issues,forest destruction thatincrease, so it is necessary to design community-based forest resources. In the human resources is less of ability from government officer as facilitator of empowerment, so it needs training plans of capacity building and competence of human resource by government apparatus.In theeconomy and social issues, there are less motivated to entrepreneurship because of the lack of available capital and economic infrastructure and the income of the community is still relatively low, so that need to develop improving access plan and strengthening socio-economic community.